Overcoming inherent narrow bandwidth and low radiation properties of electrically small antennas by using an active interior-matching circuit - Althuwayb, Ayman Abdulhadi; Alibakhshikenari, Mohammad; Virdee, Bal Singh; Falcone, Francisco; Limiti, Ernesto (IEEE, 2021)
A technique is described to extend the working frequency-band and increase the radiation gain and efficiency of an electrically small antenna (ESA). The geometry of the proposed ESA is in the shape of an “H” structure. A small gap is included at the symmetry of the H-shape structure to embed an inductive load that is used to connect the two halves of the H-shaped antenna. With the lumped element inductor, the bandwidth of the H-shaped antenna is restricted by Chu-lower bound. However, it is demonstrated by analytical analysis and through 3D full-wave electromagnetic simulations that when the inductive load is replaced with negative reactance from a negative impedance converter (NIC) the antenna’s bandwidth, radiation gain and efficiency performance can be significantly improved by ~40%, 3.6 dBi and 55%, respectively. This is because NIC acts as an effective interior matching circuit. The resonant frequency of the antenna structure with the inductive element was used to determine the required inductance variation in the NIC to realize the required bandwidth and radiation characteristics from the H-shaped antenna.